A New Method for Calculating the Stiffness of Filament Wound Composites considering the Fibre Undulation and Crossover. Issue 4 (July 2014) - Shen, Chuangshi; Han, Xiaoping; Guo, Zhangxin
The filament-winding process leads to fibre undulations and the nonorthogonality of crossover geometries into thin-shell cylinders. In this paper, the micromechanical geometry in the fibre crossover regions of filament-wound cylinders is first identified. A three-step method is then presented for calculating the stiffness of filament winding composites. In Step 1, the 3D stiffness for the undulating layer is converted to an effective 2D stiffness via the two angles, namely the filament winding angle and the inclination angle due to the fibre undulation. In Step 2, the lamination theory is used to obtain the local laminate stiffness as a function of the undulation direction and the stiffness constants through the numerical integrating and averaging along the length of undulation. In Step 3, the whole stiffness of filament winding composites is calculated through the transformation from the principal coordinate axis to the direction of filament-winding. The effects of the filament winding angles, winding sequence and filament undulating region on the stiffness are finally discussed.